Influence Of Internship Experience, Job Interest AndSelf-Efficacy On Work Readiness Of STIE Bina Karya Tebing Tinggi Students - Iqbal Affandi, Muhammad; Syahlan, Ali; Amalia, Eka; Bukhori, Miftahul; Fitriyah Nasution, Bunga (STAI Tebing Tinggi Deli, 2024)
This research aims to determine the influence of internship experience and interest work and self-efficacy towards work readiness of STIE Bina Karya students in Tebing Tinggi City. The research method used is survey research quantitative approach. The research subjects consisted of 394 active students STIE Bina Karya Tebing Tinggi City. Data collection techniques use questionnaire by distributing it to STIE Bina Karya Kota Tebing Tinggi students and documentation by taking references from books, journals and other relevant sources. Data analysis uses descriptive statistical analysis, classical assumption analysis, multiple regression analysis, hypothesis and coefficient testing determination. The research results show that there is an influence of experience internship, work interest and self-efficacy simultaneously influence work readiness students of STIE Bina Karya Tebing Tinggi City. This can be seen in Eq linear multiple regression is Y = 24.266 + 0.089X1 + 0.172X2 + 0.040X3. Based on the hypothesis test, it is known that the significance value (Sig.) is 0.000 < 0.05, and and obtained a coefficient of determination value of 0.598 (59.8%) so that it can be obtained It was concluded that internship experience, work interest and self-efficacy were significant together or simultaneously influence student work readiness STIE Bina Karya Tebing Tinggi City